2020
DOI: 10.1155/2020/8562309
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Pleuran (β‐Glucan from Pleurotus ostreatus) in the Management of Herpes Simplex Virus Type 1 Infection

Abstract: One of the highly prevalent viral pathogens among children and adults causing infection, clinically presenting as herpes labialis, is herpes simplex virus type 1 (HSV-1). The long-term administration of acyclovir, a standard regimen for therapy against HSV-1 infections, can cause viral resistance against this drug. Therefore, the development of natural drugs with low toxicity that are able to enhance host antiviral defense against HSV infection is needed. β-Glucans represent a type of biologically active molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Another mode of action could be the support of NK cell functions and modulatory effect on T cells (Bobovak et al, 2010;Bergendiova et al, 2011;Jesenak et al, 2013). A recent study confirmed the role of pleuran (β-glucan isolated from Pleurotus ostreatus) in the treatment of acute herpes simplex type 1 infection (Urbancikova et al, 2020). Using in vitro model of lung injury, lentinan (β-glucan from Lentinus edodes) reduced cytokine-induced NF-κB activation in human alveolar epithelial cells and attenuated pro-inflammatory cytokine production 6,8,22) as well as TGF-β and IL-10 (Murphy et al, 2020).…”
Section: Anti-viral Agentsmentioning
confidence: 95%
“…Another mode of action could be the support of NK cell functions and modulatory effect on T cells (Bobovak et al, 2010;Bergendiova et al, 2011;Jesenak et al, 2013). A recent study confirmed the role of pleuran (β-glucan isolated from Pleurotus ostreatus) in the treatment of acute herpes simplex type 1 infection (Urbancikova et al, 2020). Using in vitro model of lung injury, lentinan (β-glucan from Lentinus edodes) reduced cytokine-induced NF-κB activation in human alveolar epithelial cells and attenuated pro-inflammatory cytokine production 6,8,22) as well as TGF-β and IL-10 (Murphy et al, 2020).…”
Section: Anti-viral Agentsmentioning
confidence: 95%
“…Pleuran has also been tested for the management of herpes simplex virus type I infection, as the typical remedy acyclovir can cause viral resistance if used for long periods. Urbancikova et al [ 117 ] conducted a randomized, placebo-controlled clinical trial to assess the effect of this compound on the duration and intensity of herpes symptoms and the incidence rate and duration of acute respiratory symptoms and intercurrent diseases in HSV-1-positive patients. This was done in 90 patients randomly assigned to receive pleuran or placebo, and the study was divided into two phases: an acute treatment phase, lasting 10 days, in which either Immunoglukan P4H ® ACUTE (300 mg pleuran, 160 mg vitamin C, 10 mg Zn) or placebo (160 mg vitamin C, 10 mg Zn) was administered daily; and a subsequent 120-day preventive phase, with daily administration of either Immunoglukan P4H ® (100 mg pleuran, 100 mg vitamin C) or placebo (100 mg vitamin C).…”
Section: Pharmacological Activities Of Mushrooms: Medical Evidencementioning
confidence: 99%
“…It is known that β-glucan is associated with an anti-cholesterolemic activity, which is good for heart health. The β-glucan can directly inhibit and disrupt the virus particles or present its indirect effects through enhancing the immunity of the host ( Urbancikova et al, 2020 ). In a study conducted by Legentil et al (2015) , they reported that there are several evidences showing that β-glucan shares the best position among several immunomodulators materials.…”
Section: Nutrients Possessing Antiviral Propertiesmentioning
confidence: 99%
“…In a study conducted by Legentil et al (2015) , they reported that there are several evidences showing that β-glucan shares the best position among several immunomodulators materials. On the other hand, the antiviral property of β-glucan was investigated by Urbancikova et al (2020) ; the immunomodulatory β-glucan effect was observed on the herpes simplex virus type 1. The authors described that β-glucan stimulated the production of cytokines and activation of natural killer cells, T lymphocytes, and dendritic cells, leading to enhanced host immunity.…”
Section: Nutrients Possessing Antiviral Propertiesmentioning
confidence: 99%